2022
DOI: 10.1161/circoutcomes.121.008651
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and Cerebrovascular Disease Mortality in Asian American Subgroups

Abstract: Background: Asian American individuals comprise the fastest-growing race and ethnic group in the United States. Certain subgroups may be at disproportionately high cardiovascular risk. This analysis aimed to identify cardiovascular and cerebrovascular disease mortality trends in Asian American subgroups. Methods: Age-standardized mortality rates (ASMR), average annual percent change of ASMR calculated by regression, and proportional mortality ratios of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 30 publications
3
49
0
Order By: Relevance
“…This analysis demonstrates the need to better characterize the differential health risks among Asian subgroups to inform culturally specific health interventions. These observations are consistent with recently published work showing differences in CV mortality among Asian-American subgroups: Asian Indians had the highest risk of CV due to ischemic heart disease and heart failure, while the highest cerebrovascular disease mortality rate occurred among Vietnamese individuals [8] .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This analysis demonstrates the need to better characterize the differential health risks among Asian subgroups to inform culturally specific health interventions. These observations are consistent with recently published work showing differences in CV mortality among Asian-American subgroups: Asian Indians had the highest risk of CV due to ischemic heart disease and heart failure, while the highest cerebrovascular disease mortality rate occurred among Vietnamese individuals [8] .…”
Section: Discussionsupporting
confidence: 93%
“…Another NHANES study found higher acculturation level was associated with greater intake of ultra- processed foods among Asian-Americans [7] . The major Asian-American subgroups in the US include Asian Indian, Chinese, Filipino, Japanese, Koreans, and Vietnamese who have heterogeneous CV mortality rates, with the highest rates due to ischemic heart disease and heart failure occurring among Asian Indian men and women [8] . Publicly available, disaggregated Asian subgroup identification in nationally representative data from NHANES and NHIS are limited, thus presenting challenges to understand the association between acculturation level and CV risk factors among the subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…However, these results were pooled individuals of multiple Asian ethnicities, and the lack of disaggregation of Asian subgroups for risk assessment remains a significant clinical issue. There are major differences in ASCVD risk with South Asian people at substantially higher risk while most East Asian people, including Chinese-Americans, Japanese-Americans, and Korean-Americans at much lower risk [ 64 , 65 ]. Similar to Asian subgroups, those of Hispanic or Latinx origin also experience heterogeneity in ASCVD risk, with people of Puerto Rican or Caribbean descent carrying a higher risk than those of Mexican descent [ 61 ].…”
Section: Future Directionsmentioning
confidence: 99%
“…These REFs include family history of premature ASCVD, chronic kidney disease (CKD), ankle-branchial index (ABI) <0.9, triglycerides ≄175 mg/dL, low-density lipoprotein cholesterol (LDL-C) 160–190 mg/dL, metabolic syndrome (MetS), chronic inflammatory diseases, high-sensitivity C-reactive protein (hsCRP) ≄2 mg/dL, lipoprotein(a) (Lp(a)) ≄50 mg/dL, apolipoprotein B ≄ 130 mg/dL, and for women, premature menopause and pregnancy-associated conditions (e.g., preeclampsia) that increase ASCVD risk [ 1 , 2 ]. Additionally, South Asian ethnicity was identified as a REF due to the disproportionately elevated risk for premature ASCVD in this population compared with other Asian American subgroups and non-Hispanic White individuals [ 1 , [3] , [4] , [5] ].…”
Section: Introductionmentioning
confidence: 99%